EBI2 in splenic and local immune responses and in autoimmunity. Issue 2 (9th May 2018) - Barington, L; Wanke, F; Niss Arfelt, K; Holst, P J; Kurschus, F C; Rosenkilde, M M
Abstract: The seven transmembrane G protein-coupled receptor EBV-induced gene 2 (EBI2), also known as GPR183, is expressed in particular in immune cells. Activated by its endogenous ligands, which are a group of oxysterols, it functions as a chemo-attractant receptor, mediating cell migration. In coordination with other receptors, EBI2 plays important roles in controlling the migration of immune cells during the course of a T-dependent Ab response in the spleen. In recent years, it has become clear that EBI2 also has other roles to play in the immune system. Thus, EBI2 seems to be involved in innate immune responses, such as those mediated by TLR signaling, and it has been implicated in regional immune responses, including immune responses in the CNS. In this review, we describe the functions of EBI2 in B cells, T cells, and dendritic cells during the course of a T-dependent Ab response in the spleen. Furthermore, we review the existing evidence supporting a role for EBI2 in local immune responses and in autoimmune diseases, with a special focus on immune responses in the CNS. Finally, we discuss which type of role EBI2 may play in autoimmune diseases, and we give our opinion about the paths of future research in EBI2. Review on the roles of EBI2 in T-dependent antibody responses and its potential roles in local immune responses and autoimmunity.